Utilization of Industrial Flour Waste as Biobriquette Adhesive: Application on Pyrolysis Biobriquette Sawdust Red Teak Wood - Harini Wahyuni; Andi Aladin; Ruslan Kalla; Muhammad Nouman; Ardimas Ardimas; MD. Shahariar Chowdhury (CV FOUNDAE, 2022)
Biobriquette is one of the alternative fuels derived from biomass. The biomass used in this research is red teakwood charcoal. This research purposes to utilize red teakwood charcoal as alternative fuels and then to knows best characters compressive strength, ignition power and caloric value according to Indonesian quality standards (SNI 01-6235-2000). Characteristics of biobriquettes are known by test ash content, moisture content, volatile matter, fix carbon, compressive strength, ignition power and caloric value. The materials used are red teakwood plus industrial flour waste. The process of making biobriquette begins with drying the material, pyrolysis during 150 minutes at a temperature of 400 oC, sieved with 40 mesh. The briquetting was using a cube-shaped mold with manual pressure which was then dried in an oven to a constant weight and tested its characteristics by the ASTM (American standard Testing and material) method. The results showed that the added adhesive was very take effect in producing the best briquettes. The characteristics of briquettes with the best optimum adhesive composition produce is adhesive 5% charcoal 95% produce ash content 5.49% , moisture content 4.26 %, volatile matter 26.89 %, fix carbon 63.12%, compressive strength 3.64 kgf/cm2, caloric value 7038 kcal/kg, and ignition power 0.03 gram/minute categorized as passing the specifications for the quality requirements briquettes of SNI 01-6235-2000.